Keanekaragaman Jenis Kepiting Bakau Famili Ocypodidae di Kawasan Mangrove Desa Lalombi, Kec. Banawa Selatan, Kab. Donggala - Erna, Ni Kadek; Bustamin, Bustamin; Rauf, Abd.; Sutrisnawati, Sutrisnawati; Zainal, Syech; Dhafir, Fatmah (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the species diversity of mangrove crabs from the family Ocypodidae in the mangrove area of Lalombi Village, Banawa Selatan District, Donggala Regency. The type of research used is descriptive quantitative. The study was conducted in the mangrove area of Lalombi Village, Banawa Selatan District, Donggala Regency, from February to April 2025. The sampling location was determined using a purposive sampling method, considering mangrove vegetation density and site accessibility. Crab samples were collected directly using the hand collection method during low tide. The population and samples in this study consisted of all Ocypodidae mangrove crab species found at the research site. Data analysis was performed by calculating the Shannon-Wiener diversity index (H') to determine the level of species diversity. A total of five crab species were found: Uca dussumieri, Uca perplexa, Uca cryptica, Uca jocelynae, and Uca coarctata. The diversity index value of Ocypodidae mangrove crabs obtained in the Lalombi Village mangrove area was 1.098. Based on the Shannon-Wiener index category, a value of 1 â‰¤ H' â‰¤ 3 indicates moderate diversity; therefore, the value of 1.098 reflects a moderate level of diversity. This moderate diversity indicates that the mangrove ecosystem in the study area is still capable of supporting several Ocypodidae species, although it may have experienced ecological pressures such as human activities or changes in habitat quality.